Management of Dynamic Biomedical Terminologies: Current Status and Future Challenges - Da Silveira, M.; Dos Reis, J. C.; Pruski, C. (Yearbook of Medical Informatics, 2015)
Objectives: Controlled terminologies and their dependent artefacts provide a consensual understanding of a domain while reducing ambiguities and enabling reasoning. However, the evolution of a domain’s knowledge directly impacts these terminologies and generates inconsistencies in the underlying biomedical information systems. In this article, we review existing work addressing the dynamic aspect of terminologies as well as their effects on mappings and semantic annotations.Methods: We investigate approaches related to the identification, characterization and propagation of changes in terminologies, mappings and semantic annotations including techniques to update their content.Results and conclusion: Based on the explored issues and existing methods, we outline open research challenges requiring investigation in the near future.
Keywords: Knowledge management; knowledge representation; ontology evolution; biomedical ontologies